2012
DOI: 10.1371/journal.pone.0041386
|View full text |Cite|
|
Sign up to set email alerts
|

Occurrence of Natural Vertical Transmission of Dengue-2 and Dengue-3 Viruses in Aedes aegypti and Aedes albopictus in Fortaleza, Ceará, Brazil

Abstract: Background Aedes aegypti and Aedes albopictus perform an important role in the transmission of the dengue virus to human populations, particularly in the tropical and subtropical regions of the world. Despite a lack of understanding in relation to the maintenance of the dengue virus in nature during interepidemic periods, the vertical transmission of the dengue virus in populations of A. aegypti and A. albopictus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0
15

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 43 publications
4
86
0
15
Order By: Relevance
“…Coinfections have only been reported in Asian [19,20], Brazilian [20], and Peruvian [21] patients. These cases of coinfection might be related to coinfections in the mosquito vector; however, there are also few reports about mosquito coinfections, and only a few studies have demonstrated the simultaneous existence of natural serotype 2 and 3 infections in Aedes populations from Asia and America [23,24]. Additionally, the presence of intra-host competition in the vector, which may favor the replication of some viral variants over others, has been reported for other infection models, either between two serotypes of the same virus [24] or between strains of the same serotype [25], thereby favoring the transmission of one of the variants.…”
Section: Introductionmentioning
confidence: 99%
“…Coinfections have only been reported in Asian [19,20], Brazilian [20], and Peruvian [21] patients. These cases of coinfection might be related to coinfections in the mosquito vector; however, there are also few reports about mosquito coinfections, and only a few studies have demonstrated the simultaneous existence of natural serotype 2 and 3 infections in Aedes populations from Asia and America [23,24]. Additionally, the presence of intra-host competition in the vector, which may favor the replication of some viral variants over others, has been reported for other infection models, either between two serotypes of the same virus [24] or between strains of the same serotype [25], thereby favoring the transmission of one of the variants.…”
Section: Introductionmentioning
confidence: 99%
“…albopictus, respectively. During the study period, DENV-2 and DENV-3 were the predominant serotypes in the regions where the immature stages of the vector were sampled (27) .…”
Section: Discussionmentioning
confidence: 99%
“…To explore this phenomenon, several studies have been conducted recently in several regions (26) (27) (28) . Because the country spans much of the continent, dengue epidemiology may vary considerably between regions.…”
Section: Methodsmentioning
confidence: 99%
“…1 Vertical transmission of arboviruses occurs from an adult female mosquito to its eggs and progeny. This may be an important source of maintenance for arboviruses such as dengue virus [3][4][5] and West Nile virus, 6,7 particularly during unfavorable environmental conditions. Inconsistent findings are reported for the existence of vertical transmission of CHIKV; if it does occur, it is infrequent.…”
Section: Introductionmentioning
confidence: 99%